The effect of concentric-concentric isokinetic activity with restricted blood flow on serum VEGF levels in active elderly men - Maryam Nourshahi; Sajad Ahmadizad; fatemeh imani; Poone Dehghan (Shahid Beheshti University, 2021)
Purpose: Aging is a process of progressive reduction of physiological and functional factors. One of the important changes that occur during this period is the reduction of angiogenesis. Many studies have shown that sports activities can prevent the development of these factors. Therefore, the purpose of this study was to investigate the effect of concentric isokinetic activity (low intensity) with blood flow restriction on serum VEGF levels in active elderly men.  Methods: For this purpose, 10 healthy men at age range 60-80 years were selected through convenience sampling in a Tehran-based park (average weight: 77.8 ± 9.25 kg, height: 175.9 ± 2.92 cm, BMI: 25.15 ± 2.85kg/m2). Blood flow restriction was performed with a Doppler device to obtain 50% of the maximum restricted blood pressure for the session. Subjects performed four knee flexion and extension activities with 20% of one-repetition maximum and at an angular velocity of 30 degrees per second, complete flexion and extension of the leg. initially, they performed the first time with 30 repetitions and the other three times with 15 repetitions and with 30 seconds rest between each time. Before the start of the protocol, blood sampling was performed immediately and two hours after the activity, and serum VEGF was measured by ELISA. 2 × 3 repeated measures ANOVA was used to analyze the data after ensuring their normal distribution. Results: The results of data analysis showed that serum levels of VEGF, in response to concentric isokinetic activity with restricted blood flow, increased significantly compared to concentric isokinetic activity without restricted blood flow (P= 0.01). Conclusion: Therefore, it seems that in the elderly, the use of the blood flow restriction method, despite the low intensity of activity, had a significant effect on serum VEGF levels as one of the angiogenic factors in active elderly men.